Have A Sharp Tooth? A Link to Oral Cancer-A Case Series (Journal of Pharmaceutical Negative Results, 2022)
Squamous cell carcinoma of the mouth (OSCC) accounts for 90% of all oral malignancies. It is a mucosal neoplasm that is malignant. The lateral border and ventral surface of the tongue are the most typical locations. Though the cause of OSCC is unknown, tobacco and betel quid usage, heavy alcoholic drinking, a diet lacking in fresh fruits and vegetables, infections, and heredity are all thought to be common risk factors. Dentist need to be aware that oral trauma and irritations such as – sharp teeth or over-hang restorations may also lead to OSCC within the short period of time. So, early detection of OSCC in such conditions is critical for improving prognosis and lowering morbidity and mortality. As a result, we offer a case series of three patients with a white lesion who were diagnosed with OSCC caused by a sharp tooth and verified by histopathology